Reliable Callosal Measurement: Population Normative Data Confirm Sex-Related Differences - Mitchell, Tejal N.; Free, Samantha L.; Merschhemke, Martin; Lemieux, Louis; Sisodiya, Sanjay M.; Shorvon, Simon D. (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Corpus callosal cross-sectional area (CCA) may be a clinical indicator of disease progression, but factors influencing callosal morphology in healthy subjects must be determined before comparisons can be made in patients. We sought to define a reliable and easily repeatable method for CCA measurement and to examine the effects of sex, age, handedness, and cerebral volume.METHODS: Neurologically healthy volunteers (age range, 14–68 years; mean age, 32.6 years ± 12.3 [SD]; 44 men, 56 women; 87 right handed) underwent conventional MR imaging. Data were reoriented in the image space to account for intersubject variations in head position before the midsagittal plane was defined by using midpoints of the anterior commissure (AC), posterior commissure (PC), and interhemispheric fissure (IF). Midsagittal CCA and total cerebral volume were measured and correlated with sex, age, and handedness.RESULTS: The mean CCA was 6.27 cm2 ± 0.90. Women had a larger CCA proportional to cerebral volume (6.16 × 10−3 cm−1 vs 5.78 × 10−3 cm−1 in men; P = .02). The percentage difference for the CCA-cerebral volume from the group mean was +2.6% in women and −3.6% in men. Only a small linear relationship of CCA with cerebral volume was noted (r2 = 0.15), and CCA was not significantly correlated with age or handedness.CONCLUSION: To our knowledge, this is the largest study of callosal area in a community-based sample of control subjects; such subjects provide controls for future studies. Our findings provide anatomic evidence of sex differences in interhemispheric connectivity. Much CCA variability is independent of cerebral volume.